Logo, Label, and Packaging Improvement on Jamu Bu Uri Products for Digital Marketing - Kartini; Ratna Yulistiani; Dadik Raharjo; Rizky Fatkhur Rohman; Sri Alam Syah Lihan Candra Asi (Future Science, 2022)
It is quite common knowledge that some traditional herbal medicine sellers used plastic bottles of mineral water as a storage medium for their traditional herbal medicine. Even though the allotment of mineral water bottles is dispossible, it cannot be used again after the contents run out. This problem about the packaging must be addressed. When viewed from the visual aspect, the presentation of traditional herbal medicine still tends to be monotonous in terms of packaging. Whereas packaging can influence consumers to give a positive response, good packaging will optimize profits. Therefore, this service activity targets several improvements in handling packaging problems for Jamu bu Uri products, with the aim of increasing the marketing of traditional herbal products.